Estimating Tax Progressivity in Developing Countries: The Plato Index - Alex Cobham; Edmund FitzGerald; Petr Jansky (Charles University in Prague, Institute of Economic Studies (IES), 2021)
Progressive direct taxation is necessary to complement social protection, in order to reduce income inequality as well as poverty. A new metric of personal income tax incidence progressivity (the "Plato Index") is presented, using WIDER databases for income inequality (WIID) and tax revenues (GDR). Taxation is shown to be far less progressive in developing countries, than in developed ones (particularly Europe) although there are large variations within regional and income groups. There is significant correlation of direct tax progressivity not only with the level of economic development, but also with health and education provision. Both findings imply potential policy space for higher personal income tax pressure.
Keywords: D12; H23; I32; O15; 330; direct taxation; tax progressivity; developing countries; fiscal incidence; social protection; direct taxation; tax progressivity; developing countries; fiscal incidence; social protection